Improving the nutritive value of rice bran by fungal and extrusion treatments - Lim, Yi Chin (2015)
One of the limitations of the growth of poultry industry in Malaysia is the high cost of feed. Rice bran, a by-product from the rice milling process, could be used as a raw feed ingredient of poultry at a higher inclusion rate. Although rice bran is a cheaper feed material, it requires treatments to improve the nutritive value as to fufill the nutritional requirement of poultry. Poultry demands for relative higher level of soluble protein and reducing sugar. While the dietary fibre of feed for poultry should be kept at low level due to the lack of fibre digestive enzymes in poultry. This study was performed to improve the nutritive value of rice bran by fungal and extrusion treatments. Solid state fermentation (SSF) was conducted by using Rhizopus oligosporus, while the extrusion was performed by utilization of twin screw extruder. The fermentation conditions were optimized by Response Surface Methodology (RSM) with central composite design (CCD) method. Manipulated fermentation conditions were the moisture (A), incubation duration (B), incubation temperature (C) and inoculum density (D). The optimal SSF conditions obtained were 100 ml for A, 2.5 days for B, 35 °C for C and 1 X 106 spores/ml for D. The responses measured for fermented rice bran and extruded rice bran were 4.26 mg/g and 2.31 mg/g for soluble protein (SP), 11.29 mg/g and 3.97 mg/g for reducing sugar (RS), 10.9 % and 6.7 % for crude fibre (CF), 31.5 % and 21.1 % for neutral detergent fibre (NDF) respectively. The SP, RS, CF and NDF values for untreated rice bran were 2.24 mg/g, 6.35 mg/g, 7.3 % and 27.9 % respectively. Study showed that fermention and extrusion were the approaches to improve the nutritive value of rice bran